Area-Selective Atomic Layer Deposition for Resistive Random-Access Memory Devices - Oh, Il Kwon; Khan, Asir Intisar; Qin, Shengjun; Lee, Yujin; Wong, H. S.Philip; Pop, Eric; Bent, Stacey F. (ACS Applied Materials and Interfaces, 2023)
Resistive random-access memory (RRAM) is a promising technology for data storage and neuromorphic computing; however, cycle-to-cycle and device-to-device variability limits its widespread adoption and high-volume manufacturability. Improving the structural accuracy of RRAM devices during fabrication can reduce these variabilities by minimizing the filamentary randomness within a device. Here, we studied area-selective atomic layer deposition (AS-ALD) of the HfO2 dielectric for the fabrication of RRAM devices with higher reliability and accuracy. Without requiring photolithography, first we demonstrated ALD of HfO2 patterns uniformly and selectively on Pt bottom electrodes for RRAM but not on the underlying SiO2/Si substrate. RRAM devices fabricated using AS-ALD showed significantly narrower operating voltage range (2.6 × improvement) and resistance states than control devices without AS-ALD, improving the overall reliability of RRAM. Irrespective of device size (1 × 1, 2 × 2, and 5 × 5 μm2), we observed similar improvement, which is an inherent outcome of the AS-ALD technique. Our demonstration of AS-ALD for improved RRAM devices could further encourage the adoption of such techniques for other data storage technologies, including phase-change, magnetic, and ferroelectric RAM.
Keywords: Area selective; Area-selective atomic layer deposition; Atomic-layer deposition; Data storage; Data storage devices; Filament confinement; High volumes; Neuromorphic computing; Random access memory; Resistive random-access memory; area-selective atomic layer deposition; data storage device; dielectrics; filament confinement; resistive random-access memory